Temporal Progression of Recognition Memory Impairment, Astrogliosis, and Cholinergic Dysfunction in the Streptozotocin Rat Model of Sporadic Alzheimer’s Disease - Niño Rivero, Sofía (2025)
The streptozotocin (STZ) experimental model of sporadic Alzheimer’s disease (SAD), the most prevalent form of this type of dementia, has become a valuable tool to study the behavioral and morphological changes that occur during the gradual development of this pathology. We used the STZ experimental model in combination with the novel object recognition test (NORT) and immunohistochemical techniques to evaluate the recognition memory decline and morphological alterations in memory-related structures (hippocampus and cortex). Our analysis included five different time points after intracerebroventricular (ICV) administration of 3 mg/kg of STZ or artificial cerebrospinal fluid (aCSF) as a control. The time points included three distinct stages: early (15 and 30 days), intermediate (60 days), and late (90 and 120 days). We found that recognition memory impairment started in the intermediate stage and persisted through the later stages. Morphologically, we detected significant astrogliosis starting in the early stages, whereas cholinergic changes began in the intermediate stage. No neuronal loss was observed at any of the time points analyzed. Our results further support the hypothesis that astrogliosis constitutes an initial pathological event that may compromise the hippocampal cholinergic system and can contribute to the onset of recognition memory deficits.